THE POSITION OF BORU DIAMPUAN IN THE CUSTOMS OF THE BATAK TOBA ETHNIC GROUP IN SIALANGUAN VILLAGE PANGURURAN DISTRICT - Ratih Baiduri; Marlina T Sinaga (Universitas Negeri Medan, 2025)
This study aims to analyze the position of boru diampuan in the customs of the Toba Batak ethnicity, analyze the challenges faced by the boru diampuanin the customs of the Toba Batak ethnicity. This research uses a qualitative method with an ethnographic approach. The location of the research was conducted in Sialanguan Village, Pangururan District, Samosir Regency. The data collection technique in this study was through participant observation, in-depth interviews, documentation, and field notes. The results of the study showed that the son-in-law who lived in his wife's village was caused by economic limitations while living in Perantaun so he chose to return to his wife's village. There are three positions of boru diukah in customs , namely low social status, playing the role of parhobas (servants of traditional events), and not having the right to the inheritance of the in-laws. The position of boru diampuan in customs poses several challenges faced by boru diampu, namely disadvantaged social status, psychological challenges, and conflicts in agricultural land use. The phenomenon of boru diampuan in Sialanguan Village results in gender inequality because it shows a more dominant role and requires sacrifice from the boru diampuan, namely the son-in-law of the man who lives in his wife's village. Gender inequality can be seen when prioritizing men (hula-hula) and placing boru diamukah as a member of parhobas (servants) or who are always marginalized in the in-laws' families. Keywords: Toba Batak Ethnicity, Boru Diampuan, Dalihan Natolu, Boru Diampuan's Role, Gender Inequality